2021
DOI: 10.1038/s41377-020-00435-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive dynamic range shift (ADRIFT) quantitative phase imaging

Abstract: Quantitative phase imaging (QPI) with its high-contrast images of optical phase delay (OPD) maps is often used for label-free single-cell analysis. Contrary to other imaging methods, sensitivity improvement has not been intensively explored because conventional QPI is sensitive enough to observe the surface roughness of a substrate that restricts the minimum measurable OPD. However, emerging QPI techniques that utilize, for example, differential image analysis of consecutive temporal frames, such as mid-infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(56 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…We could not observe extraordinary signals, for example, higher than four times that of the monolayer even when there was a strong coupling between the layers, as confirmed by the PL measurements. This is contrary to the behavior of the twisted bilayer graphene, which exhibits a large enhancement in the third-harmonic generation [ 37 ]. In addition, the peak angle ( φ s ) in the twisted region exhibits a value that follows the relation φ s = ( φ 1 – φ 2 )/2, as indicated by the dashed line in Figure 3 c. The relatively large deviation for θ twist > 40° is likely due to errors originating from weak signals, which originates from the destructive interference.…”
Section: Resultsmentioning
confidence: 78%
“…We could not observe extraordinary signals, for example, higher than four times that of the monolayer even when there was a strong coupling between the layers, as confirmed by the PL measurements. This is contrary to the behavior of the twisted bilayer graphene, which exhibits a large enhancement in the third-harmonic generation [ 37 ]. In addition, the peak angle ( φ s ) in the twisted region exhibits a value that follows the relation φ s = ( φ 1 – φ 2 )/2, as indicated by the dashed line in Figure 3 c. The relatively large deviation for θ twist > 40° is likely due to errors originating from weak signals, which originates from the destructive interference.…”
Section: Resultsmentioning
confidence: 78%
“…After the discovery of graphene, it has been widely studied and investigated in various scientific research fields because of its distinctive nonlinear optical properties [ 31 , 54 , 136 ]. The features of broadband optical absorption, ultrafast carrier recovery, gapless band structure, and high damage threshold make graphene one of the leading SAs in the application of fiber laser lasers.…”
Section: Ultrafast Fiber Laser Based On Ld Samentioning
confidence: 99%
“…All of these LD-based tunable devices could also be investigated for various in-line all-fiber devices, such as ultrafast all-optical tunable switchers, optical limiters, all-optical modulators, polarizers etc., based on electrically/optically controlled nonlinear optical properties (i.e., higher-order susceptibility/nonlinearity, multiphoton absorption, etc.). The twist-angle in Bi-layer LD materials also can be engineered along with the externally (electrically and/or optically) controlled scheme to find the enhanced higher-order optical nonlinearity and SA properties for high performance, ultrafast and precisely controlled fiber lasers, and other nonlinear optical devices [ 54 ]. LD SA-based fs mode-locked ultrafast fiber lasers have grown emerging interest in space-borne applications, as they can sustain more than the life span of satellites [ 136 , 208 , 209 ].…”
Section: Prospects For Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleitez et al ( 32 ) demonstrated mid-IR photoacoustic microscopy with broad biomedical applications for monitoring carbohydrates, lipids, and proteins in cells and tissues. The Ideguchi group ( 62 ) recently reported the MIP quantitative phase imaging with depth-resolved capability and extended dynamic range ( 63 ).…”
Section: Introductionmentioning
confidence: 99%